2013
DOI: 10.1007/s00270-013-0795-8
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Intra-Arterial Therapy via the Cystic Artery for Hepatocellular Carcinoma

Abstract: Purpose To evaluate the postprocedural imaging findings and safety of repeated intra-arterial therapy via the cystic artery in patients with hepatocellular carcinoma (HCC). Methods This retrospective study was approved by our institutional review board. From February 2002 to January 2012, we performed repeated (two or more) chemotherapeutic infusion or chemoembolization via the cystic artery using iodized oil in 132 patients with HCCs. Computed tomographic (CT) scans, digital subtraction angiograms, and medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Superselective chemoembolization or chemoinfusion at the deep branch of the cystic artery is relatively safe [ 74 ]. Chu et al [ 75 ] reported that transient or persistent gallbladder wall thickening was the most frequent CT finding following 340 sessions of intra-arterial therapy through the cystic artery. In their study, acute cholecystitis was observed in only two patients, who responded well to conservative management.…”
Section: Hepatobiliary Complicationsmentioning
confidence: 99%
“…Superselective chemoembolization or chemoinfusion at the deep branch of the cystic artery is relatively safe [ 74 ]. Chu et al [ 75 ] reported that transient or persistent gallbladder wall thickening was the most frequent CT finding following 340 sessions of intra-arterial therapy through the cystic artery. In their study, acute cholecystitis was observed in only two patients, who responded well to conservative management.…”
Section: Hepatobiliary Complicationsmentioning
confidence: 99%
“…Bleeding originating from the cystic artery may be associated with surgical cholecystectomy, hemorrhagic cholecystitis, gallbladder cancer, and prior percutaneous drainage of the gallbladder (6)(7)(8)(9). Several case studies have documented the successful use of TAE in treating cystic artery bleeding (6)(7)(8)(9), and embolization procedures through the cystic artery have been safely attempted for the management of hepatocellular carcinoma (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%